Impact of educational outreach intervention on enhancing health care providers' knowledge about statin therapy prescribing in Malaysian patients with type 2 diabetes mellitus - Elnaem, Mohamed Hassan Abdelaziz; Nik Mohamed, Mohamad Haniki; Huri, Hasniza Zaman; Mohd Shah, Azarisman Shah (Wiley, 2018)
Rationale Previous research reported underutilization of statin therapy among patients with type 2 diabetes mellitus. Improving health care providers' awareness and understanding of the benefits and risks of statin treatment could be of assistance in optimizing the statin prescribing process.